Evaluation of haemato-biochemical changes associated with ciprofloxacin therapy in canine pyoderma - Jessy V (Department of Veterinary Biochemistry, College of Veterinary and Animal Sciences, 2008)
The present study was undertaken with the objective to assess the haemato-biochemical changes following prolonged ciprofloxacin therapy in dogs affected with pyoderma. The study was conducted in dogs presented to the Veterinary College Hospital, Mannuthy, during the period from August 2007 to March 2008. Among the twenty one dogs studied, twelve completed the full course of antibiotic therapy and post treatment evaluation. The pyoderma confirmed dogs were treated with ciprofloxacin @ 10 mg/kg body weight once daily orally for a period of 14 days. Blood samples collected on day 0, 7 and 14 of treatment and fifth day after the completion of therapy was subjected to haemato-biochemical analysis.